2004
DOI: 10.1142/s0192415x04001758
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Improves Aspects of Spatial Performance in Ovariectomized Rats

Abstract: The present study was designed to investigate the ameliorating effects of Cnidiuim monnieri L. Cusson (CM) and osthole, a constituent of CM, on the spatial performance deficit in scopolamine (SCOP)-treated or ovariectomized (OVA) rats. CM improved the deficit of spatial performance, and reversed the lower plasma estradiol levels caused by SCOP in female rats. In addition, osthole (3 and 10 mg/kg, s.c.) improved the performance deficit in OVA rats. It (10 and 30 micrograms/brain, icv) also improved the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…In summary, the results of the present study and our previous report (Hsieh et al, 2004) proved that CM ameliorated the impairment of inhibitory avoidance learning performance and Morris water maze induced by SCOP in male and female rats. Then, osthole, isolated from petroleum ether layer of CM (Cai et al, 2000), also ameliorated the memory deficit induced by SCOP (Shen et al, 1999;Hsieh et al, 2004) and might be a major ingredient of CM on memory-improving effect.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In summary, the results of the present study and our previous report (Hsieh et al, 2004) proved that CM ameliorated the impairment of inhibitory avoidance learning performance and Morris water maze induced by SCOP in male and female rats. Then, osthole, isolated from petroleum ether layer of CM (Cai et al, 2000), also ameliorated the memory deficit induced by SCOP (Shen et al, 1999;Hsieh et al, 2004) and might be a major ingredient of CM on memory-improving effect.…”
Section: Discussionsupporting
confidence: 85%
“…Some pharmacological reports suggest that CM possesses estrogen-like and anti-senescent effects (Liu et al, 2005;Zhang et al, 2006). Our previous study found petroleum ether layer of CM and its ingredient -osthole could alleviate scopolamine-induced amnesia via its estrogen-like property in female rats (Hsieh et al, 2004). The series reports of Qin pointed out its total coumarins and ingredient -osthole ameliorated learning impairment and strengthened the function of pituitary-adrenocortical axis in Kidney-Yang deficiency rats induced by continuous administration of hydrocortisone acetate (Qin et al, 1997a;Qin et al, 1997b).…”
Section: Introductionmentioning
confidence: 98%
“…Osthol is an important coumarin compound for its extensive medical activities including anti-inflammatory (Liu et al 2005), antitumor (Chou et al 2007), prevention of atherosclerosis (Ogawa et al 2007), anti-aging (Hsieh et al 2004), and antiproliferative (Guh et al 1996) properties. Osthol also has been used to control crop insects (Xia et al 2009;Ya et al 2006) and pathogenic bacterium Huang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Ost has various pharmacological and biological applications, and current research is focused on its antitumor activity. Several previous studies have reported that Ost is effective in inducing cell apoptosis, arresting cell cycle, and inhibiting cell proliferation.…”
Section: Introductionmentioning
confidence: 99%